Measurement of elastic strains and small lattice rotations using electron back scatter diffraction. - Wilkinson, A (1996)
A method is presented for the determination of elastic strains from electron back scatter diffraction patterns, which are obtained at high spatial resolution, from bulk specimens in a scanning electron microscope. It is estimated that the method is sensitive to strains of the order of 0.02%. Strains in Si(1-x)Ge(x) epitaxial layers grown on planar Si substrates were measured for x from 0.2 to 0.015, there being excellent agreement with X-ray diffraction results. Small lattice rotations can also be measured, the technique being sensitive to rotations of 0.01 degrees, which offers an improvement of approximately two orders of magnitude from the more usual EBSD measurements of misorientation. Small lattice rotations were measured in Si(0.85)Geo(0.15) grown on a patterned Si substrate and were consistent with elastic relaxation of the epilayer strain energy.